Law as Information in the Era of Data-Driven Agency. - Hildebrandt, Mireille (Modern Law Review, 2016)
This contribution introduces the mathematical theory of information that 'informs' computer systems, the internet and all that has been built upon it. The aim of the author is to invite lawyers to reconsider the grammar and alphabet of modern positive law and of the Rule of Law, in the face of the alternative grammar and alphabet of a data-driven society. Instead of either embracing or rejecting the technological transitions that reconfigure the operations of the law, this article argues that lawyers should collaborate with the computer scientists that engineer and design the affordances of our new onli fe world. This is crucial if we want to sustain democratic participation in law-making, contestability of legal effect and transparency of how citizens may be manipulated by the invisible computational backbone of our rapidly and radically changing world.